The Rise of China: Toward Sanctuary. - Admussen, Nick (Chinese Literature & Thought Today, 2025)
This essay historicizes, contextualizes, and interprets the politics of the often-cited "rise of China," finding its origins in the early twentieth-century palingenetic imagination and its geographic and ideological spread to be wide and varied. Once the concept rose to ascendance between the 1970s and 1990s, the essay argues that it became an often-obligatory story about China's importance to readers of Chinese literature in English translation, one that is often inserted into translational paratexts by editors. This process centers elite readers, instructs attention to nationalist politics and frames of reference, and suppresses individual and small-group readerly desires. The essay ends by applying Khairani Barokka's idea of the sanctuary translation to argue that the power of ableist, nationalist, and ethnonationalist metanarratives to frame translation work can be opposed and overcome by careful attention to who translations are not intended to reach or serve.